Auditoria de gestión y su relación con el cumplimiento del presupuesto de ventas de la empresa electrodomésticos Núñez, cantón Quevedo, año 2014 - Chuez Palacios, Janeth Alexandra (2016)
The management audit consists on an independent exam to an entity, with the purpose of evaluating the effectiveness of the administration in connection with the general objectives; and its efficiency like organization; with the purpose of elaborating a report on the global situation and on the management performance. The present investigation has as fundamental objective, to carry out a management audit and its relationship with the execution of the budget of sales of the company Núñez, Appliances Canton Quevedo, year 2014, this purpose it was necessary the use of the techniques and tools characteristic of the audit, the questionnaire method was applied to evaluate the five internal check components that establishes the COSO I model, in which it was determined that the company is in a confidence level from 82% equivalent to % to a high level and in a level of risk of 18% corresponding to a low level. When evaluating the different operational activities through the administration indicators it was found that the company is in acceptable levels of, efficiency and effectiveness, as for the budget of sales it was verified that it is accomplished in 96.57%. After the management audit was finished, a report was elaborated, in which the results of the audit were obtained, identifying clearly the most important aspects that involve the normal performance of the activities of the company. Based on the actual evaluation, it was recommended focusing on the administration basic processes and organization, programming the respective action plans and correction of the negative aspects found as weaknesses of the internal check, implementing the group of recommendations showed in the final report of audit.